L’efficacité d’images de la série sur l'enseignement de l'écriture des étudiants du semestre II dans La section de la pédagogie de français - Uchi Mely Viani; Dwi Astuti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
The purpose of this study was to test the effectiveness of the use of serial image carriers in writing for students in the second semester of the French Language Education Program. The research method used in this study was a "one-group pre-test-post-test design", The respondents who participated in this study amounted to 41 students in the second semester of the French Language Education Program. Data collection techniques use testing methods in the form of pre-tests and post-tests. This study uses the validity of the content to determine the reliability of this correlation formula of the moment produced, before being used to take data, the finding aid was tested on 5 students, from the test the value of r is 0.994, while r table is 0.87, so that it can be said that the instrument is valid and reliable. Data collection results in the pre-test obtained a mean value is 53.90, while in the post-test is 60.97. The results of the calculations show that t count > t table is 3.325 > 1.684, with db is 40 at a significance level of 5%. The hypothesis is therefore accepted, which means that the use of serialized image carriers is used in learning to write French among students in semester II.